Perbandingan Kekuatan Mengikat dan Eksekutorial Akta Perdamaian Notaris dengan Acta Van Dading Pengadilan Perspektif Kepastian Hukum - Hanif Abdi Firdaus; Bobby Tanumihardja; Firza Fahriza Prayoga Putra; Audi Febriwidhia Aulia (Jurnal Hukum Lex Generalis, 2026)
This study examines the differences in binding force and executorial power between notarial settlement deeds and court settlement deeds (acta van dading) within the framework of legal certainty. The research is motivated by the existence of two forms of dispute resolution through settlement that produce different legal consequences, particularly in terms of enforcement. The objective of this study is to analyze the binding force of notarial settlement deeds and the binding as well as executorial force of court settlement deeds, and to compare both instruments in ensuring legal certainty for the parties. This research applies a normative legal method using statutory and conceptual approaches. The findings indicate that notarial settlement deeds bind the parties contractually as authentic deeds with perfect evidentiary value, yet they do not possess executorial force. In contrast, court settlement deeds have executorial power equivalent to final court judgments, allowing direct enforcement. The absence of executorial force in notarial deeds creates a disparity in legal protection and enforcement effectiveness. The study concludes that court settlement deeds provide stronger legal certainty compared to notarial settlement deeds.